Optimization of response surface methodology for the extraction of isoliquiritigenin from Aspergillus niger solid-state fermentation of licorice and its antitumor effects - Hao, Jingwei; Li, Qiuxuan; Dong, Nan; Zhou, Yi; Sun, Yifan; Pei, Yingying; Zhou, Xiangkun; Yang, Lei (Frontiers in Pharmacology, 2025)
This research focused on optimizing the extraction of isoliquiritigenin (ISL) from licorice via a solid-state fermentation process involving Aspergillus niger. Isoliquiritigenin was quantified through high-performance liquid chromatography (HPLC), initially assessed with one-way analysis and optimized using the Box-Behnken response surface method. The extracted isoliquiritigenin underwent structural modification, and the modified derivatives with enhanced activity were screened for in vivo antitumor efficacy using the MTT Colorimetric (MTT) assay. Finally, the structural and compositional alterations in the intestinal flora of the mice were evaluated post-administration of the extracted isoliquiritigenin. The results indicated that the optimal extraction conditions were pH 3.7, a solid-liquid ratio of 1:2, and an Aspergillus niger inoculum concentration of 1.5 × 106, yielding 1.53 mg/g of isoliquiritigenin after fermentation for 4 days. This yield was 9 times greater than that obtained through conventional reflux extraction and 5.46 times higher than that from the ultrasonic extraction method. Nuclear Magnetic Resonance (NMR) analysis of isoliquiritigenin (ISL) and its derivatives revealed that the ISL-b high dose group exhibited the most significant tumor suppression effect, with a suppression rate of 56.3%. In the mouse model following drug intervention, histopathological examination of kidney tissue via HE staining demonstrated that the safety profile of ISL-b was superior. Studies on the intestinal flora of mice revealed that the number of species was higher in the ISL-b high-dose group. Furthermore, there were significantly more species in the community samples than in the model group, with Micrococcus wartii accounting for the largest percentage at 24.49%. In the ISL-b dosing group, there was a significant increase in the abundance of Akkermansia muciniphila and Bradyrhizobium at the species level. The discoveries offer a robust scientific groundwork for developing antitumor drugs derived from isoliquiritigenin and enhance the broader application of licorice, a traditional herbal remedy.